Timescapes when everything happens all at once: Educator temporalities in an unequal crisis - Feldman, Jennifer; Czerniewicz, Laura (Proceedings of the International Conference on Networked Learning, 2024)
This paper focuses on aspects of time and educators’ timescapes during the Covid-19 pandemic. It contributes to a larger discussion about changing discourses and practices of temporality both during and after a crisis, especially those enabled by technology and neoliberal contexts. Situated within the unequal and diverse South African landscape where the pandemic overturned traditional educational timescapes, the paper explores the experiences of educators from different education settings - rural, urban, school, higher education and provincial education departments and considers three interrelated questions: What did educators' timescapes look like during the crisis of the pandemic? What was the role of technology in changing educators’ timescapes? How were educational inequities manifest in the timescapes which emerged? To analyse the educators’ experiences of time, teaching with technology and networked learning during the pandemic, the paper draws on Adam’s (1998, 2004, 2021) theorisation of time. Adam argues that time is relational and composed of irreducible elements that are not always easily visible. Experiences of how time is represented or visualised include temporality, tempo and timing, as well as the past, present and future. None of the elements of time operate in isolation; they mutually implicate one another highlighting the ways in which we perceive and interpret time in our lives and the world around us. The paper discussion highlights the use of technology and networked learning linked to pedagogical changed routines and organisation that made educators readily available to their students when face-to-face interaction was not possible. While this was beneficial to students (and parents), this resulted in a blurring or conflation of educators’ work and personal lives. Educators describe experiencing time and space as scrambled, compressed and/or porous, having to negotiate new rhythms and patterns of work that require reorganising and managing their lives differently. In addition, educators reported experiencing an intensification of time and work during this period, as they struggled with the pace and tempo of teaching and learning in varied education contexts. In conclusion, the paper suggests that the unique historical circumstances of the pandemic created particular conditions for online learning with some of the technologies rapidly inserted into the education system during this period remaining uncritically in place, further highlighting the need for ongoing research in areas of time, technology and networked learning, especially in diverse and varied educational settings.